A Systematic Review on Factors Associated With Percutaneous Bone Anchored Hearing Implants Loss. Issue 10 (December 2018) - Bezdjian, Aren; Smith, Rachel Ann; Thomeer, Henricus G.X.M.; Willie, Bettina M.; Daniel, Sam J.
Abstract : Objective: To investigate factors associated with percutaneous bone anchored hearing implant (BAHI) loss. Data Sources: Africa-Wide, Biosis, Cochrane, Embase, Global Health, LILACs, Medline, Pubmed, and Web of Science electronic databases. Study Selection: All studies reporting on adult and/or pediatric patients with a BAHI loss were identified. Retrieved articles were screened using predefined inclusion criteria. Eligible studies underwent critical appraisal for directness of evidence and risk of bias. Studies that successfully passed critical appraisal were included for data extraction. Data Extraction: Extracted data included study characteristics (study design, number of total implants and implant losses, follow-up), patient characteristics (sex, age, comorbidities, previous therapies), and information regarding BAHI loss (etiology of loss, timing of occurrence). Data Synthesis: From the 5, 151 articles identified at the initial search, 847 remained after title and abstract screening. After full text review, 96 articles were eligible. Fifty-one articles passed quality assessment, however, due to overlapping study population, 48 articles reporting on 34 separate populations were chosen for data extraction. Three hundred one implant losses occurred out of 4, 116 implants placed, resulting in an overall implant loss occurrence rate of 7.3%. Failed osseointegration was responsible for most implant losses (74.2%), followed by fixture trauma (25.7%). Most losses due to failed osseointegration occurred within 6 months of the implantation. BAHI implant loss occurred more frequently in pediatric patients ( p < 0.005). Conclusion: The current systematic review identified factors associated with BAHI loss. These factors should be considered when assessing patients' candidacy and when investigating reasons for impeded implant stability and loss. Abstract : Supplemental Digital Content is available in the text